A beginning teacher's experience in creating a podcast in a popular pre-ENEM - Pimentel, Amanda Duarte; Heckler, Valmir (Debates em Educação, 2026)
This article reports in narrative form a stage of action research developed during a doctorate in Science Education, focusing on the teaching practice of a beginning teacher in the context of a popular pre-ENEM. Using narrative methodology, the study investigated the challenges and potential of the process of creating podcasts as a pedagogical tool. The emerging results in writing show that, in addition to developing communication and research skills in students, the production of podcasts promoted reflections on structural inequalities and the integration of technologies in teaching. Furthermore, the use of narrative as an analysis methodology allowed the teacher in training to articulate the theory and practice of being a teacher, allowing the construction of knowledge to emerge from the experiences shared between the educator and students. This work highlights the relevance of active methodologies in the collaborative construction of knowledge, overcoming logistical and educational barriers.